Immunochemistry in Clinical Laboratory Medicine : Proceedings of a symposium held at the University of Lancaster, March, 1978 - Ward, A.M.; Whicher, J. (Springer Netherlands, 1979)
The rapid growth of specific protein estimations in the clinical laboratory over the last 10 years has been due to advances both in methodology and in the understanding of the role of the various plasma proteins in health and disease. This expansion has been made possible by the development of both gel phase and fluid phase techniques for the estimation of proteins and the ready availability of antisera to individual plasma proteins. The specificity of the immunological reaction has allowed the more precise identification and estimation of individual plasma proteins than was possible with dye binding or other chemical techniques, but at the same time these methods have introduced other possible errors and pitfalls. Advances in understanding of the structure and function of various plasma proteins has pointed the way to new clinical applications of plasma protein estimation in the diagnosis and monitoring of disease. The Symposium, of which these are the proceedings, was planned to bring together a number of experts in the field to discuss the available methods and their clinical application